The Effect of Working Capital Management Effectiveness and Fixed Asset Management Efficiency on the Financial Performance of Anutapura Regional Hospital, Palu City - Stella Maria Wentinusa; A Rohendi; Juli Asril (Research of Service Administration Health and Sains Healthys, 2026)
This study aims to analyze the effect of working capital management effectiveness and fixed asset management efficiency on the financial performance of RSUD Anutapura Palu. The independent variables used are Working Capital Turnover (WCT) and Fixed Asset Turnover (FAT), while financial performance is measured using Return on Fixed Assets (ROFA). A quantitative approach was employed, using multiple linear regression analysis based on financial report data from 2017 to 2022. The results indicate that WCT and FAT simultaneously have no significant effect on ROFA, as shown by a significance value of 0.906 (> 0.05), thus rejecting the alternative hypothesis. These findings suggest that other factors such as high operational costs, fluctuations in BPJS revenue, and the lack of integration of financial indicators into strategic planning documents have a more dominant influence on financial performance. Therefore, improvements in integrated financial management systems and the implementation of result-based budgeting principles are necessary to enhance efficiency and ensure the hospital's financial sustainability.